Effects of Physical Parameters of Multiphase Flow on Fire Water Monitor Based on Fluent - Yuan, Xiaoming; Zhao, Shiyi; Chu, Wang; Zhang, Lijie (IET Conference Proceedings, 2018)
To improve the jet performance of a fire water monitor, the monitor head with three different inner contour lines were designed. Based on FLUENT, the calculation domain was defined geometrically and then the cloud pictures of the flow velocity, pressure, turbulence kinetic energy and multiphase flow of the fluid field in the nozzle and jet were obtained, based on which the optimal structure of each model can be selected. The simulation result can provide the theoretical reference for the design of a monitor head.